Semi–automated standardisation of melanin bleaching procedures of heavily pigmented melanocytic lesions for immunohistochemical analysis on an automated platform. Issue 4 (2nd October 2019) - Orchard, GE; Gabriel, J; Shams, M; Fernando, P; Satoc, J; Nwokie, T; Ismail, F; d'Amico, C
ABSTRACT: Background : The diagnosis of heavily pigmented melanocytic lesions is problematic. This is often compounded by lack of visibility of nuclear detail of tumour cells due to physical masking by melanin pigment. Similarly, there can be colour merging of chromogenic final reaction products with melanin, making an evidence of antigenic localisation problematic. There are a number of melanin bleaching techniques available for immunohistochemical assessments. Material and methods : All methods to date have involved the bleaching of melanin as a manually performed primary step before loading subsequently bleached slides onto automated immunohistochemical platforms. Here we define a semi-automated bleaching procedure that allows full integration on one of the most widely employed automated IHC staining platforms (Roche Ventana BenchMark Ultra). The bleaching protocol was defined on the BenchMark Ultra and involved the assessment of 24 histological cases of heavily pigmented malignant melanoma lesions (13 cutaneous and 11 metastatic) routinely fixed processed and paraffin wax embedded. Results : Completion of the bleaching was assessed on H&E preparations performed following the semi-automated bleaching step and employing the Roche Ventana BenchMark Ultra machine for 60 min at 42°C. Complete immunohistochemical staining was achieved on the automated platform within 5–6 h including the bleaching step. Results were consistent across all tissue evaluated. Discussion : This data provides evidence that the hydrogen peroxide bleaching procedure can be adapted for integration on one of the most widely employed automated IHC staining platforms and as a result, improve the efficiency and reproducibility of the technique.